Endeavour to Survive in Patricia McCormick's Novel Never Fall Down (2012) - Esron Simarmata; Muhd Al-Hafizh (Universitas Negeri Padang, 2019)
This thesis is the analysis of a novel which written by Patricia McCormick entitled Never Fall Down (2012). It explores the issue of endeavour to survive which reflected by the main character. It is also intended to find out the contribution of fictional devices such as character, plot (conflict), and setting in revealing the issue of endeavour to survive. This analysis is related to the concept of life instinct which developed by Sigmund Freud that is supported by the text-based and context-based interpretation. The result of this analysis shows about the way the main character survive in dealing with any situation in his life by changing his mindset and behaviour.